Analisis Penerapan kurikulum Merdeka Pada Mata Pelajaran IPAS Kelas IV di SD 3 Gulang - Yourdamarta, Putri AMP; Fina Fakhriyah,; Khamdun, (PESHUM : Jurnal Pendidikan, Sosial dan Humaniora, 2025)
The aim of this research is to analyze the application of the independent curriculum in class IV science learning. Science in the independent curriculum is the lesson content of a combination of science and social studies which are put together. Science and Technology is a subject that contains a lot of theory and memorizes several scientific terms in its learning. This is the reason why many students of secondary education sometimes feel bored and lack enthusiasm in participating in science learning in class, especially now that in the independent curriculum it is combined with social studies learning, which makes social sciences a lesson that contains a lot of theory. The method used in this research is a qualitative method. The qualitative method is a research method that examines a problem or object through various studies. The data obtained from this research is based on observations, interviews, and also literature reviews from various sources for the validity of the data in the research. The results of this research are that with the implementation of the independent curriculum at the elementary school level, especially in science and science learning, students have enthusiasm in participating in learning because students are directly involved, not only listening to theory but also carrying out practical activities. This can be seen from (1) children being more enthusiastic in participating in learning; (2) children look more active and not just listeners; (3) children are more enthusiastic and better able to understand the material presented; (4) effective implementation of the independent curriculum in IPAS